Videollamadas por celular: aprendizajes y desafíos en la infancia temprana. - Ramírez, Laura; De Benedictis, Carla; Quiroga, Macarena; Rosemberg, Celia (Enunciación, 2026)
Widespread access to various technologies has led to new forms of interaction. While passive screen use has been negatively associated with children's language development, video calls may involve a type of engagement that could support communicative exchanges. This study analyzes how children aged 2 to 6 use the cellphone camera during family video-calls, aiming to describe the multimodal strategies employed to sustain communication. A qualitative analysis was conducted on 24 video-calls, which were segmented and coded using ELAN software. Different configurations of device use were identified: phone resting on a surface, held by an adult, or held by the child. Across all configurations, children integrate visual information into the interaction--bringing objects closer, moving the camera, or giving directions to the interlocutor--although the level of autonomy and control over the device increases with age. Younger children tend to lose track of framing and require more adult mediation, while older children demonstrate a more conscious and coordinated use. These findings indicate that videocalls, when supported by a more experienced partner, can foster interactions in which children participate actively.